Simple electrophysiological predictor of QRS change induced by cardiac resynchronization therapy: A novel marker of complete left bundle branch block - Sedláček, Kamil; Jansová, Helena; Vančura, Vlastimil; Grieco, Domenico; Kautzner, Josef; Wichterle, Dan (Heart rhythm, 2021)
BACKGROUND: QRS complex shortening by cardiac resynchronization therapy (CRT) has been associated with improved outcomes. OBJECTIVE: We hypothesized that the absence of QRS duration (QRSd) prolongation by right ventricular mid-septal pacing (RVP) may indicate complete left bundle branch block (cLBBB). METHODS: We prospectively collected 12-lead surface electrocardiograms (ECGs) and intracardiac electrograms during CRT implant procedures. Digital recordings were edited and manually measured. The outcome measure was a change in QRSd induced by CRT (delta CRT). Several outcome predictors were investigated: native QRSd, cLBBB (by using Strauss criteria), interval between the onset of the QRS complex and the local left ventricular electrogram (Q-LV), and a newly proposed index defined by the difference between RVP and native QRSd (delta RVP). RESULTS: One hundred thirty-three consecutive patients were included in the study. Delta RVP was 27 ± 25 ms, and delta CRT was -14 ± 28 ms. Delta CRT correlated with native QRSd (r = -0.65), with the presence of ECG-based cLBBB (r = -0.40), with Q-LV (r = -0.68), and with delta RVP (r = 0.72) (P < .00001 for all correlations). In multivariable analysis, delta CRT was most strongly associated with delta RVP (P < .00001), followed by native QRSd and Q-LV, while ECG-based cLBBB became a nonsignificant factor. CONCLUSION: Baseline QRSd, delta RVP, and LV electrical lead position (Q-LV) represent strong independent predictors of ECG response to CRT. The absence of QRSd prolongation by RVP may serve as an alternative and more specific marker of cLBBB. Delta RVP correlates strongly with the CRT effect on QRSd and outperforms the predictive value of ECG-based cLBBB.
Keywords: Predictive Value of Tests; Heart Conduction System; elektrofyziologické techniky kardiologické; senioři; Electrophysiologic Techniques, Cardiac; Aged; Male; funkce levé komory srdeční; lidé; Treatment Outcome; Humans; tepový objem; převodní systém srdeční; prediktivní hodnota testů; Ventricular Function, Left; Stroke Volume; Outcome predictors; Heart Ventricles; srdeční komory; blokáda Tawarova raménka; Electrocardiography; Cardiac Resynchronization Therapy; Cardiac resynchronization therapy; mužské pohlaví; výsledek terapie; Left bundle branch block; následné studie; prospektivní studie; ženské pohlaví; srdeční resynchronizační terapie; Follow-Up Studies; Female; Heart failure; Bundle-Branch Block; Prospective Studies